Antifungal Activity of Kinar (Kleinhovia hospita L.) Leaf Ethanol Extract Against Malassezia furfur - Wakano, Muhammad Zaid; Astuty, Eka; Manuputty, Amanda Gracia (Folia Medica Indonesiana, 2022)
Highlights : • Alternative medicine is needed for pityriasis versicolor because there are recurrence cases and resistance to antifungal agents. • Kinar leaf ethanol extract cannot inhibit the growth of Malassezia furfur. • Further studies are suggested on the type of solvent and appropriate concentration to attract more bioactive compounds. Abstract : Pityriasis versicolor is a superficial dermatomycosis that can decrease human self-confidence. This infection is caused by the fungus Malassezia furfur. Eighty percent of recurrence cases after treatment and resistance to antifungal agents were found. Therefore, alternative medicine is needed. Kinar (Kleinhovia hospita Linn.) is a tropical plant that have bioactive compounds, such as alkaloids, flavonoids, tannins, and saponins. The purpose of this study was to determine the effectiveness of kinar leaf extract against the growth of Malassezia furfur. This research was a laboratory experimental study using paper disc diffusion method. Kinar leaves (green and yellow leaves) were macerated using 96% ethanol and made into concentrations of 10%, 20%, 40%, 60%, 80%, and 100%. As much as 200 mg of ketoconazole was used as a positive control and distilled water as a negative control then tested on Malassezia furfur using Sabouraud dextrose agar (SDA). The parameter observed was the clear zone formed around the paper disc. The tests and observations showed that there was a clear zone formed around the paper disc. It means that the kinar leaf extract cannot inhibit the growth of Malassezia furfur.